(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article provides a theoretical and practical analysis of the level of methodological preparation required for future oligophrenopedagogues to conduct effective professional activities within an inclusive education environment. Working in an inclusive setting demands that specialists possess not only specialized pedagogical knowledge but also competencies in differential approaches, the development of individual education programs (IEPs), the design of correctional-developmental sessions, and pedagogical collaboration. The study examines students’ methodological competencies, their level of adaptation to inclusive environments, skills in adapting educational materials, and proficiency in organizing correctional activities. As effective ways to enhance methodological preparation, the article recommends strengthening practical training and implementing case studies, project-based learning, and reflective technologies. The research findings serve to modernize the system of preparing future special education teachers for inclusive education within higher education frameworks.